2023
DOI: 10.3390/ijms241512483
|View full text |Cite
|
Sign up to set email alerts
|

IL-23/IL-17 Axis in Chronic Hepatitis C and Non-Alcoholic Steatohepatitis—New Insight into Immunohepatotoxicity of Different Chronic Liver Diseases

Ankica Vujovic,
Andjelka M. Isakovic,
Sonja Misirlic-Dencic
et al.

Abstract: Considering the relevance of the research of pathogenesis of different liver diseases, we investigated the possible activity of the IL-23/IL-17 axis on the immunohepatotoxicity of two etiologically different chronic liver diseases. A total of 36 chronic hepatitis C (CHC) patients, 16 with (CHC-SF) and 20 without significant fibrosis (CHC-NSF), 19 patients with non-alcoholic steatohepatitis (NASH), and 20 healthy controls (CG) were recruited. Anthropometric, biochemical, and immunological cytokines (IL-6, IL-10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Research findings in the field of basic medical sciences have demonstrated the significant role of inflammation during chronic HCV infection [12]. Some inflammation-inducing proteins could potentially serve as indicators of inflammation in patients with CHC [13]. Interleukin (IL)-6 and IL-8, C-X-C motif ligand (CXCL)-9, CXCL-10, CXCL-12, and macrophage migration inhibitory factor (MIF) have the potential to function as indicators for evaluating the advancement from chronic hepatitis to cirrhosis [14][15][16].…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…Research findings in the field of basic medical sciences have demonstrated the significant role of inflammation during chronic HCV infection [12]. Some inflammation-inducing proteins could potentially serve as indicators of inflammation in patients with CHC [13]. Interleukin (IL)-6 and IL-8, C-X-C motif ligand (CXCL)-9, CXCL-10, CXCL-12, and macrophage migration inhibitory factor (MIF) have the potential to function as indicators for evaluating the advancement from chronic hepatitis to cirrhosis [14][15][16].…”
Section: Chronic Inflammationmentioning
confidence: 99%